Levels of influence of parasites on the human immune system - Soatova Xolnisa Raxmat qizi; Shodmonov Jamshid Anvar o‘g‘li; Umbarov Javohir Halil o‘g‘li; Temirova O‘g‘iloy Umidillo qizi; Asadullayev Asliddin Alisher o‘g‘li (Zien Journals, 2023)
Immunity is a protective reaction of the body. Currently, the study of the immune process is of great importance in medicine. Because the body is fighting against disease processes in the body through immune response reactions. This depends on the self-recovery and protection of the body. These are special protective cells (T and B lymphocytes, antibodies and antigens, through immunocomponents).
Keywords: Immunity; Antigens; Antibodies; lymphocytes